Perancangan Hotel Resort Di Kawasan Wisata Pantai Soge Pacitan Dengan Penerapan Arsitektur Tropis - Adhwaa Hanifah; Karya Subagya; Anggraeni Dyah S. (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
This Soge Beach Resort Hotel is the first 5-star Resort Hotel in the city of Pacitan. Because the city of Pacitan has quite attractive tourist destinations, and also very beautiful natural potential, this has led to many foreign and local tourists arriving, but the accommodation facilities are inadequate, so this Soge Beach Resort Hotel was designed. Designing a Resort Hotel using the concept of Tropical Architecture is the right alternative for this Resort Hotel because the city of Pacitan is quite hot, because Tropical Architecture is a type of architecture that provides answers or adaptations of building forms to the effects of tropical climates. Keywords: Hotel Resort, Pacitan City, Tropical Architecture.